Practical considerations for laboratories: Implementing a holistic quality management system - Pillai, Segaran; Calvert, Jennifer; Fox, Elizabeth (Frontiers in Bioengineering and Biotechnology, 2022)
A laboratory quality management system (LQMS) is an essential element for the effective operation of research, clinical, testing, or production/manufacturing laboratories. As technology continues to rapidly advance and new challenges arise, laboratories worldwide have responded with innovation and process changes to meet the continued demand. It is critical for laboratories to maintain a robust LQMS that accommodates laboratory activities (e.g., basic and applied research; regulatory, clinical, or proficiency testing), records management, and a path for continuous improvement to ensure that results and data are reliable, accurate, timely, and reproducible. A robust, suitable LQMS provides a framework to address gaps and risks throughout the laboratory path of workflow that could potentially lead to a critical error, thus compromising the integrity and credibility of the institution. While there are many LQMS frameworks (e.g., a model such as a consensus standard, guideline, or regulation) that may apply, ensuring that the appropriate framework is adopted based on the type of work performed and that key implementation steps taken is important for the long-term success of the LQMS and for the advancement of science. Ultimately, it ensures accurate results, efficient operations, and increased credibility, enabling protection of public health and safety. Herein, we explore LQMS framework options for each identified laboratory category and discuss prerequisite considerations for implementation. An analysis of frameworks’ principles and conformity requirements demonstrates the extent to which they address basic components of effective laboratory operations and guides optimal implementation to yield a holistic, sustainable framework that addresses the laboratory’s needs and the type of work being performed.